Plants used for Socio-Magico-Religious purposes by the indigenous communities of Sub-Himalayan Tract, Uttarakhand - Gairola, Sumeet; Singh, Kanwaljeet; Jyotsana Sharma (Ethnobotany Research and Applications, 2022)
Background: Plants play an essential role in every rural society's cultural and religious ceremonies. The focus of the study was to document the use of plants by the indigenous communities of sub-Himalayan Tract, Uttarakhand in magico-religious practices. Method: Information was extracted from eighty informants (50 men; 30 women) between 25 to 75 years of age. A semi-structured questionnaire, interviews, and participatory observations were made to collect data from the informants to meet the study's requirements. Results: The present study revealed 34 plants belonging to 31 genera and 25 families for the magico-religious practices. Fruits and whole plants are mainly used to conduct various social and religious practices, such as offerings in religious ceremonies. Herbs (59%) were the dominant forms, and wastelands (48%) were the dominant source of magico-religious plants. High Informant Consensus Factor (Fic) was recorded for the plants used in the sacred and religious rites (SAR) category. Species such as Datura stramonium, Ocimum tenuiflorum, Ficus benghalensis, Cynodon dactylon, Achyranthes aspera, and Calotropis procera were culturally most important based on cultural index value. Conclusion: The plant species play a vital role in practicing the religion and culture among the studied communities. Therefore, it is suggested that the indigenous communities of the sub-Himalayan region be monitored and contacted regularly about their beliefs. They must be informed and made aware of the importance of plant diversity and the significant loss that will occur if it is lost. Keywords: Uttarakhand, Indigenous communities, Magico-religious practices, Cultural Importance, Plants